2020
DOI: 10.1186/s12888-020-02923-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of one-to-one peer support in mental health services: a systematic review and meta-analysis

Abstract: Background Peer support is being introduced into mental health services internationally, often in response to workforce policy. Earlier systematic reviews incorporate different modalities of peer support (i.e. group and one-to-one), offer inconsistent evidence of effectiveness, and also indicate substantial heterogeneity and issues of quality in the evidence base at that time. An updated review, focussed on one-to-one peer support, is timely given current policy interest. This study aims to systematically revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
152
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 69 publications
6
152
2
3
Order By: Relevance
“…[2][3][4] These newly minted mental health professionals were eventually integrated into a number of services in various mental healthcare settings, such as to support people with mental health conditions 5 , severe mental illnesses 4 6 and substance use issues. 7 Systematic reviews [8][9][10][11][12] supported these individual findings and demonstrated the effectiveness of integrating peer support workers into larger care teams. As a result of the benefit they bring to multidisciplinary care models, they have been integrated into community mental health teams 13 14 and supported employment teams 15 , where their presence is counted towards increased programme fidelity.…”
Section: Introductionmentioning
confidence: 83%
“…[2][3][4] These newly minted mental health professionals were eventually integrated into a number of services in various mental healthcare settings, such as to support people with mental health conditions 5 , severe mental illnesses 4 6 and substance use issues. 7 Systematic reviews [8][9][10][11][12] supported these individual findings and demonstrated the effectiveness of integrating peer support workers into larger care teams. As a result of the benefit they bring to multidisciplinary care models, they have been integrated into community mental health teams 13 14 and supported employment teams 15 , where their presence is counted towards increased programme fidelity.…”
Section: Introductionmentioning
confidence: 83%
“…Our previous study did show that recovery-oriented treatment (i.e., Illness Management and Recovery), is associated with higher perceived support for personal recovery (article in press), and another study has shown that service users enrolled in Assertive Community Treatment (ACT) programs are highly satisfied with the care they receive, including those being on a CTO [ 40 ]. Other interventions with a significant evidence base to support recovery include 19 randomised controlled trials of peer support work [ 41 ], 27 randomised controlled trials of the Individual Placement and Support approach to employment [ 42 ] and the development of education initiative called Recovery Colleges in 22 countries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study did show that recovery-oriented treatment (i.e., Illness Management and Recovery), is associated with higher perceived support for personal recovery (article in press), and another study has shown that service users enrolled in Assertive Community Treatment (ACT) programs are highly satis ed with the care they receive, including those being on a CTO (39). Other interventions with a signi cant evidence base to support recovery include 19 randomised controlled trials of peer support work (40), 27 randomised controlled trials of the Individual Placement and Support approach to employment (41) and the development of education initiative called Recovery Colleges in 22 countries (42).…”
Section: Discussionmentioning
confidence: 99%